Relative contributions of urbanization and greenhouse gases concentration on future climate over Beijing–Tianjin–Hebei region in China - Zheng, Zhiyuan; Dong, Wenjie; Yan, Dongdong; Guo, Yan; Wei, Zhigang; Chou, Jieming; Zhu, Xian; Wen, Xiaohang (Climate dynamics, 2022)
In this study, the effects of land use/cover (LULC) change induced by urbanization and greenhouse gases (GHGs) concentration on future climate over the Beijing–Tianjin–Hebei region in China under Representative Concentration Pathways 4.5 (RCP4.5) scenario are investigated. The Weather Research and Forecasting model is used to downscale and predict the future climate state using the RCP4.5 simulations from the Community Earth System Model. Results show that large-scale general atmospheric circulation and GHGs are the two dominate factors for the future climate over the Beijing–Tianjin–Hebei region in the next 10–20 years under the RCP4.5 scenario. Urbanization over a small-scale region and scattered areas has a slight effect on the regional future climate. On the urban local scale, the LULC change in the urban area has a relatively obvious impact on the local climate of the city through altering the land–atmosphere interaction within the urban region accompanied with seasonal dependence. The annual mean surface air temperature (SAT) of urban area is projected to be 0.44 °C (2020), 0.87 °C (2030), and 1.48 °C (2040) higher than the climatology under different climate scenarios in the future resulting from integrated urbanization and GHGs forcing effects. The annual mean SAT of urban area changed by the GHGs forcing will increase by 0.35 °C (2020), 1.00 °C (2030), and 1.66 °C (2040), and the urbanization forcing will increase the annual mean SAT by 0.09 °C (2020), − 0.13 °C (2030), and − 0.18 °C (2040) in the urban area, respectively. The effects of urban expansion on the seasonal mean SAT are different during different the warm and cold periods of a year. The expanded urban area will increase the SAT during the warm period of a year (from March to September), and will decrease the SAT during the cold period of a year (from October to February of next year). The effects of scattered urbanization process and large-scale urban agglomeration on regional and local climate have strong spatial and temporal scale dependence. GHGs are the most important factor for dominating the future climate of this region. Meanwhile, due to the important impact of urbanization on the urban local scale, we strongly suggest that urbanization process should be considered in climate modeling system since it can provide a more realistic and reliable scenario of the future climate in the urban area.